Land Registration, Governance, and Development : Evidence and Implications for Policy - Deininger, Klaus; Feder, Gershon (World Bank, 2012)
The developmental impact of institutions to establish and maintain secure property rights to land has been a subject of much debate. The authors review the literature on the impact of land administration interventions in specific contexts, highlighting the dependence of outcomes on the governance environment, the effectiveness of the state apparatus, and the distribution of socio-economic power. There is evidence, albeit not uniform, of enhancement of tenure security through land registration with benefits manifesting themselves in higher levels of investment and productivity and a reduced need to defend land rights. Land registration has also been shown to increase activity in land rental markets, leading to higher efficiency overall. Evidence of improved access to credit, due to formalization of land rights, is scant. Even in situations where land registration had positive benefits, the literature contains little rigorous analysis of cost-effectiveness and long-term sustainability of impacts. The authors conclude that formalization of land rights should not be viewed as a panacea and that interventions should be decided only after a careful diagnosis of the policy, social, and governance environment. If intervention is justified, the performance of land administration systems needs to be benchmarked in terms of coverage, cost-effectiveness, and quality of service provision.